Women's Work and Family Profiles over the Lifecourse and their Subsequent Health Outcomes. Evidence for Europe - Thomas Leoni; Rainer Eppel (WWWforEurope, 2013)
The reconciliation of family and work is one of the "new social risks" contemporary welfare states are challenged to address. This paper contributes to a better understanding of the roles of work and family in women's life trajectories, shedding light on determinants and welfare outcomes of different combinations of motherhood and employment. We identify and compare distinctive life-course employment profiles of mothers across 13 European countries. After analyzing selection patterns, we investigate the possible link that exists between these work-family profiles up to the age of 50 and subsequent health outcomes. We embed our empirical investigation in a comparative welfare state framework and differentiate between four geographical areas that can be associated with different types of European welfare state regimes.
Keywords: I1; J2; 330; Welfare state; gender; family and work; health